2015
DOI: 10.3389/fnhum.2015.00001
|View full text |Cite
|
Sign up to set email alerts
|

Causal reasoning with forces

Abstract: Causal composition allows people to generate new causal relations by combining existing causal knowledge. We introduce a new computational model of such reasoning, the force theory, which holds that people compose causal relations by simulating the processes that join forces in the world, and compare this theory with the mental model theory (Khemlani et al., 2014) and the causal model theory (Sloman et al., 2009), which explain causal composition on the basis of mental models and structural equations, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
352
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(373 citation statements)
references
References 68 publications
(118 reference statements)
19
352
2
Order By: Relevance
“…Whether this lateral-ventral distinction reflects further functional subdivisions within the anterior-ventral CMS, requires further investigation. Nonetheless, our results in AD are compatible with previous reports of both posterior and anterior-ventral CMS activity during the retrieval of self-referenced relative to non-self-referenced stimuli in healthy adults (Fossati et al, 2004; Leshikar & Duarte, 2013; Yaoi, Osaka, & Osaka, 2015). On a broader level, the involvement of both posterior and anterior-ventral CMS subregions is also consistent with the pattern of CMS activity during inherently self-related memory processes such as autobiographical memory retrieval (Addis, McIntosh, Moscovitch, Crawley, & McAndrews, 2004; Maguire, 2001; Svoboda, McKinnon, & Levine, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Whether this lateral-ventral distinction reflects further functional subdivisions within the anterior-ventral CMS, requires further investigation. Nonetheless, our results in AD are compatible with previous reports of both posterior and anterior-ventral CMS activity during the retrieval of self-referenced relative to non-self-referenced stimuli in healthy adults (Fossati et al, 2004; Leshikar & Duarte, 2013; Yaoi, Osaka, & Osaka, 2015). On a broader level, the involvement of both posterior and anterior-ventral CMS subregions is also consistent with the pattern of CMS activity during inherently self-related memory processes such as autobiographical memory retrieval (Addis, McIntosh, Moscovitch, Crawley, & McAndrews, 2004; Maguire, 2001; Svoboda, McKinnon, & Levine, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Within the brainstem and cerebellum (both receivers of afferent spinal inputs18, 48), the interpretation of the association between trauma‐induced atrophy rate and light touch and pinprick outcome is more complex. In addition to Wallerian degeneration of ascending fiber pathways that arise from the spinal cord, transsynaptic changes affecting the structure and function of sensory relay nuclei in the brainstem and neurons within the cerebellum (eg, Purkinje cells) occur as a consequence of deafferentation 18, 21, 60. The relationship between greater cerebellar atrophy rate and worse pinprick outcome is therefore interesting, as the cerebellum may also be involved in trauma‐induced maladaptive processing of afferent sensory inputs (eg, nociception)61 alongside its role as a comparator for errors in somatosensory processing62 resulting in motor impairment 48.…”
Section: Discussionmentioning
confidence: 99%
“…Cross‐sectional studies in chronic SCI have shown that sensory impairment and neuropathic pain below the level of the lesion correlated with structural10, 11, 12, 13, 14, 15 and functional changes16, 17 within the sensory system. However, such cross‐sectional studies in chronic SCI do not allow for assessment of the spontaneous evolution of structural and functional changes attributable to (1) the acute onset of deafferentation,18, 19, 20 (2) spontaneous partial sensory recovery, or (3) relearning of compensatory approaches relevant for activities of daily living (ie, visual inputs) 21. Therefore, there is only limited knowledge about the temporal dynamics and specificity of trauma‐induced structural changes and their link to the arising sensory impairment and outcome and below‐level neuropathic pain within the spinal cord, brainstem, and brain 22…”
mentioning
confidence: 99%
“…Unifying the models proposed by Kodituwakku and Olson and colleagues provides strong theoretical support for multi-component interventions integrating pharmacotherapy, child-focused training in self-regulation, and family-focused intervention targeting the pattern of parent-child interactions, parenting self-efficacy and stress, and family needs. When funding permits, researchers should consider measuring intervention effects at levels of analysis beyond standard cognitive and behavioral measures, such as changes in brain structure or function (e.g., magnetic resonance imaging, event related potentials, e.g., [1618]), physiological regulation or reactivity (e.g., cortisol, vagal tone, e.g., [19]), or observations of interpersonal functioning. Examination of moderators will also help identify for whom interventions are most effective and can guide the most efficient deployment of interventions and further efforts to improve interventions for whom they are less effective.…”
Section: Theoretical Models For Fasd Interventionmentioning
confidence: 99%
“…Compared to children on the waitlist, children who received the intervention demonstrated improvements in some aspects of inhibitory control and socioemotional functioning based on child testing and parent report. Changes in brain structure were also documented in the intervention group, including increases in gray matter in several regions of the frontal lobe and anterior cingulate [16]. Wells and colleagues [48] developed a group-based program that incorporates aspects of the Alert curriculum and treatment strategies used with children with traumatic brain injuries.…”
Section: Evidence From Empirically Studied Interventionsmentioning
confidence: 99%